2021
DOI: 10.1038/s41598-021-90548-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling analysis of the N6-methyladenosine-modified circular RNA transcriptome in cultured cells infected with Marek’s disease virus

Abstract: Marek’s disease virus (MDV) induces severe immunosuppression and lymphomagenesis in the chicken, its natural host, and results in a condition that investigated the pathogenesis of MDV and have begun to focus on the expression profiling of circular RNAs (circRNAs). However, little is known about how the expression of circRNAs is referred to as Marek’s disease. Previous reports have is regulated during MDV replication. Here, we carried out a comprehensive profiling analysis of N6-methyladenosine (m6A) modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…While previous studies have reported on the expression of host circRNAs during MDV infection ( 20 , 47 ), no study has addressed the expression of MDV-encoded circRNAs until now. Thus, we investigated MDV-encoded circRNAs from two transcriptional units involved in viral pathogenesis and tumorigenesis, namely, the meq oncogene and the LATs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While previous studies have reported on the expression of host circRNAs during MDV infection ( 20 , 47 ), no study has addressed the expression of MDV-encoded circRNAs until now. Thus, we investigated MDV-encoded circRNAs from two transcriptional units involved in viral pathogenesis and tumorigenesis, namely, the meq oncogene and the LATs.…”
Section: Resultsmentioning
confidence: 99%
“…The bioinformatic pipeline was also applied to another set of high-throughput RNAseq data obtained from an independent experiment investigating MDV in vitro productive infection and focusing on host circRNAs dysregulation ( 47 ). This RNAseq data set (accession number GSE166240 ) from infected chicken embryo fibroblasts (CEF) was processed to map back-spliced junctions over the MDV genome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the m 6 A modification may regulate the immune system to facilitate viral replication ( 53 ). We have also reported alterations in transcriptome-wide m 6 A modification in chicken lncRNAs and circRNAs ( 54 , 55 ). Recently, we found spatiotemporal changes of mRNA m 6 A modification in distinct MDV infection phases (unpublished data).…”
Section: Discussionmentioning
confidence: 75%